Risk Aversion and Investment Intentions of Filipino Investors: A Moderation Study - John Mark S Distor; Alfonce Martin V Sanchez; Jubeth Magturo; Crystal Corales; John Jasper Lazamana (Diversitas Journal, 2023)
A survey was conducted amongst a sample of Filipino retail investors residing in NCR. All at the ages of 21-60 with at least 1 year of investing experience in the Philippine stock market and cryptocurrency market. Risk Aversion, Long Term Investment Intention (LTII), and Short Term Investment Intention (STII) are the variables that were measured using Risk Aversion Scale and Investment Intentions Scale and moderation analysis of the setting of stocks and cryptocurrency was done. The study showed significant correlation of Risk Aversion and STII in the setting of cryptocurrency. The data manifested significant moderation in Risk Aversion and LTII in the setting of stock investing and Risk Aversion and STII in the setting of cryptocurrency investing.